Influence of the effectiveness of raw materials on the reliability of thermoelectric cooling devices. Part I: single-stage TEDs - V. P. Zaikov; V. I. Meshcheryakov; A. A. Gnatovskaya; Yu. I. Zhuravlev (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Increase of the reliability of information systems depends on the reliability improvement of their component elements, including cooling devices, providing efficiency of thermally loaded components. Thermoelectric devices based on the Peltier effect have significant advantages compared with air and liquid systems for thermal modes of the radio-electronic equipment. This happens due to the absence of moving parts, which account for the failure rate. The article presents research results on how thermoelectric efficiency modules affect the failure rate and the probability of non-failure operation in the range of working temperature of thermoelectric coolers. The authors investigate a model of relative failure rate and the probability of failure-free operation single-stage thermoelectric devices depending on the main relevant parameters: the operating current flowing through the thermocouple and resistance, temperature changes, the magnitude of the heat load and the number of elements in the module. It is shown that the increase in the thermoelectric efficiency of the primary material for a variety of thermocouple temperature changes causes the following: maximum temperature difference increases by 18%; the number of elements in the module decreases; cooling coefficient increases; failure rate reduces and the probability of non-failure operation of thermoelectric cooling device increases. Material efficiency increase by 1% allows reducing failure rate by 2.6 – 4.3% in maximum refrigeration capacity mode and by 4.2 – 5.0% in minimal failure rate mode when temperature difference changes in the range of 40 – 60 K. Thus, the increase in the thermoelectric efficiency of initial materials of thermocouples can significantly reduce the failure rate and increase the probability of failure of thermoelectric coolers depending on the temperature difference and the current operating mode.